Success factor of new product launch by printing and publishing business in Malaysia - Nurul Ashykin Abd Aziz; Siti Fariha Muhamad; Afifah Hanim Md Pazil; Nurul Aien Abd Aziz; Noreen Noor Abd Aziz (2015)
Printing and Publishing Business is the the main magazine and newspaper producer in Malaysia. Research that conducted will focusing on determining the success factor of new product launch . It identify the most significant success factor which influence the success of the new product launch.Success of the new product launch were found to be related to the factor of promotional which can be measure through advertising and sales promotion and the factor of supply chain and distribution can be measure by supply chain and information. According to the finding, there have a significant and positive relationship between the promotional and success of the new product launch whereby the correlation between both variables is moderately correlate. Compare with supply chain and distribution, there have a significant and positive relationship between the supply chain and distribution and success of the new product launch. The correlation between the this independent variable and dependent variable is high correlate. The research found that all the independents variables which is promotional and supply chain and distribution can explained the dependent variable which is success of the new product launch due to the high value of R². The implications from this research, Printing and Publishing Busienss can be able to easily identify the areas in which improvement is needed in the future and the result can be implement by this business in order to gain profit and became the main producer in publishing industries.